2014
DOI: 10.1177/1535370213517615
|View full text |Cite
|
Sign up to set email alerts
|

Human urinary bladder regeneration through tissue engineering – An analysis of 131 clinical cases

Abstract: Replacement of urinary bladder tissue with functional equivalents remains one of the most challenging problems of reconstructive urology over the last several decades. The gold standard treatment for urinary diversion after radical cystectomy is the ileal conduit or neobladder; however, this technique is associated with numerous complications including electrolyte imbalances, mucus production, and the potential for malignant transformation. Tissue engineering techniques provide the impetus to construct functio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
53
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
10

Relationship

6
4

Authors

Journals

citations
Cited by 64 publications
(54 citation statements)
references
References 58 publications
1
53
0
Order By: Relevance
“…Although the idea was conceived in the 1950s, and a plethora of natural and synthetic biomaterial scaffolds has been used in experimental animals, their clinical application remains a formidable challenge 139. In a meta-analysis of 28 preclinical and two clinical studies, the reviewers found a poor correlation between the initial experimental successes in healthy animals and those reported in clinical trials 140.…”
Section: Surgery To Promote Urine Storagementioning
confidence: 99%
“…Although the idea was conceived in the 1950s, and a plethora of natural and synthetic biomaterial scaffolds has been used in experimental animals, their clinical application remains a formidable challenge 139. In a meta-analysis of 28 preclinical and two clinical studies, the reviewers found a poor correlation between the initial experimental successes in healthy animals and those reported in clinical trials 140.…”
Section: Surgery To Promote Urine Storagementioning
confidence: 99%
“…More recently, it has been suggested that it could be employed to promote bladder regeneration after cancer of this tissue. Certainly, there is the possibility of using such material as a biologically tolerated matrix in experimental cell transplantations [15].…”
Section: Methodsmentioning
confidence: 99%
“…Traditional bladder tissue repair materials contain an autologous nonurinary system, such as gastrointestinal tract tissue, and synthetic polymers or nature derivative materials, such as poly hydroxy acetic acid and collagen. [1] Recent tissue engineering researches of bladder repair and reconstruction have got a remarkable progress. [2] The establishment of tissue engineering bladder is mainly based on 3 major technologies that are the appropriate seed cells, the appropriate scaffold materials, the implantation of seed cells with scaffold materials and induced into target tissue or organ.…”
Section: Introductionmentioning
confidence: 99%